Annual Report (2001-02) on the Working of State Electricity Boards & Electricity Departments - Planning Commission (Planning Commission, 2002)
This Chapter gives an overall view of the Report and highlights some of the important parameters and crucial issues relating to the power sector in the country. The subsequent chapters bring out detailed analysis of various issues and large variations in the performance of SEBs and EDs. Chapter 2 gives details of the plan outlays and expenditure in the power sector, distribution of power sector outlay between various activities viz. generation, transmission and distribution, renovation and modernisation etc. and also gives the power balances as well as the elasticity of electricity generation and consumption with respect to the GDP.
Planning Commission (Power & Energy Division) Government of India
Planning Commission (Power & Energy Division) Government of India